The histone variant Sl_H2A.Z regulates carotenoid biosynthesis and gene expression during tomato fruit ripening. (1st April 2021) - Yang, Xuedong; Zhang, Xuelian; Yang, Youxin; Zhang, Hui; Zhu, Weimin; Nie, Wen-Feng
Abstract: The conserved histone variant H2A.Z is essential for transcriptional regulation; defense responses; and various biological processes in plants, such as growth, development, and flowering. However, little is known about how H2A.Z affects the developmental process and ripening of tomato fruits. Here, we utilized the CRISPR/Cas9 gene-editing system to generate a sl_hta9 sl_hta11 double-mutant, designated sl_h2a.z, and found that these two mutations led to a significant reduction in the fresh weight of tomato fruits. Subsequent messenger RNA (mRNA)-seq results showed that dysfunction of Sl _H2A.Z has profound effects on the reprogramming of genome-wide gene expression at different developmental stages of tomato fruits, indicating a ripening-dependent correlation between Sl _H2A.Z and gene expression regulation in tomato fruits. In addition, the expression of three genes, SlPSY1, SlPDS, and SlVDE, encoding the key enzymes in the biosynthesis pathway of carotenoids, was significantly upregulated in the later ripening stages, which was consistent with the increased contents of carotenoids in sl_h2a.z double-mutant fruits. Overall, our study reveals a role of Sl _H2A.Z in the regulation of carotenoids and provides a resource for the study of Sl _H2A.Z-dependent gene expression regulation. Hence, our results provide a link between epigenetic regulation via histone variants and fruit development, suggesting a conceptual framework to understand how histone variants regulate tomato fruit quality.